IMPLEMENTATION OF E-GOVERNMENT IN PUBLIC SERVICES: A CASE STUDY ON THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF BONE DISTRICT - Sakir, Ahmad Rosandi; Almahdali, Humairah; Amaliah, Yusriah (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2024)
E-Government (Electronic Government) refers to initiatives aimed at developing the administration of government by leveraging electronic technology. This concept involves restructuring management systems and workflows within the government environment by optimizing the use of information and communication technology. E-Government is not merely about using technology to modernize governance; it is also a strategy to achieve cost efficiency and effectiveness. Moreover, its goal is to provide ease in government service facilities and grant public access to information. One of the regencies in Indonesia implementing E-Government is located in South Sulawesi, namely Bone Regency. Within the framework of E-Government implementation in Bone Regency, one of the government institutions adopting it is the Department of Population and Civil Registration of Bone Regency. The legitimacy of this system has been affirmed through Regional Regulation (Perda) No. 3 of 2017 concerning Population Administration. The E-Government program implemented in the Department of Population and Civil Registration of Bone Regency is known as the Population Administration Information System (SIAK). This research employs a qualitative approach, aiming to describe real phenomena or events. The research type applied is descriptive research using the "case study" method. The goal of this research is to provide a detailed description of the nature, character, and background of a study. Based on the research and discussion above regarding the implementation of E-Government in Public Services at the Department of Population and Civil Registration of Bone Regency, three successful elements can be concluded. The first element is support, the second is capacity, and the third is value.